Effects of Vitrectomy on Recurrent Macular Edema due to Branch Retinal Vein Occlusion after Intravitreal Injection of Bevacizumab - Tatsuya Yunoki; Keiichi Mitarai; Shuichiro Yanagisawa; Tsuyoshi Kato; Nobuo Ishida; Atsushi Hayashi (Journal of Ophthalmology)
Purpose. To evaluate the effects of pars plana vitrectomy (PPV) on recurrent macular edema due to branch retinal vein occlusion (BRVO) after intravitreal injections of bevacizumab (IVB). Methods. This retrospective study included 22 eyes of 22 patients who underwent single or multiple IVB injections for macular edema due to BRVO and showed a recurrence of macular edema. All patients then underwent PPV and were followed up for more than 6 months after the surgery with examinations of best corrected visual acuity (BCVA) and optical coherence tomography (OCT). OCT parameters were central macular thickness (CMT) and average retinal thickness in a 1-mm-diameter circular region at the fovea (MRT). Results. Mean BCVA, CRT, and MRT were significantly improved from the baseline after PPV. Greater improvement of BCVA, CRT, and MRT was obtained after 1 month of IVB than after 6 months of PPV. No eyes showed worsening of macular edema after the surgery. Conclusion. PPV improved BCVA and recurrent macular edema due to BRVO, but PPV that was less effective than IVB had been in the same patients. PPV may be one of the treatment options for recurrent macular edema due to BRVO after IVB.